Preparation of Non Locomotor Basic Movement Assessment Instruments for Class III Moderate Mentally Retarded Children at SLB Negeri Luragung Kuningan - Ratnawulan, Teti; Sadiyatu Nur Adhimah (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Assessment is an access used to determine the abilities, difficulties and needs of a child which is then used as a reference to develop an appropriate learning program. A teacher, especially a teacher who handles children with special needs, is required to be able to compile assessment instruments that are suitable for the children he handles. The purpose of this study was to develop a non-locomotor basic motion assessment instrument for class III moderate mental retardation child at SDLB SLB Negeri Luragung. Non-locomotor basic movements are used in learning activities usually in warming up or cooling down during sports that contain motion patterns such as bending, twisting, swinging and bending. This study used a qualitative approach and descriptive method. The data in this study were obtained from observations, interviews, FGDs, and validation. The results of observations made by research to three grade III moderate mental retardation child show that children experience obstacles in gross motor non-locomotor basic movements such as in sports lessons during warm-ups the child looks stiff and less able to maintain body balance so as not to fall, while in daily activities maintaining body balance while doing activities in place is very necessary. Therefore, researchers are interested in compiling a non-locomotor basic motion assessment instrument for grade III moderate disability children to find out more about what the child's difficulties are in basic non-locomotor movements, then the results of the assessment instruments that have been prepared are validated to determine readability and applicability.